The ability of Silybum marianum to phytoremediate cadmium and/or diesel oil from the soil. Issue 8 (3rd July 2018) - Hammami, Hossein; Alaie, Ebrahim; Dastgheib, Seyed Mohammad Mehdi
ABSTRACT: Phytoremediation is a new ecological and cost-effective technology applied for cleaning heavy metals and total petroleum hydrocarbon contaminated (TPH-contaminated) soils. This study was conducted to evaluate the potential of milk thistle (Silybum marianum) to phytoremediate cadmium (Cd (II)) from contaminated soils. To this end, the investigators applied a completely randomized design with the factorial arrangement and four replications. The results indicated that all the evaluated parameters of S. Marianum, including shoot and root fresh and dry weight, as well as shoot and root Cd, were significantly influenced by Cd (II) concentration and diesel oil (DO). The Cd-contaminated soil showed minor declining effects on the produced plant biomass, whereas the DO-contaminated soil had more inhibitory effects. Moreover, the soil contaminated with both Cd and DO led to adverse effects on the plant biomass. The shoot and root Cd concentration had an increasing trend in the presence of DO as the bioconcentration factor (BCF) by 1.740 (+90.78%), 1.410 (+36.89%), 2.050 (+31.41%), 1.68 (+32.28%), and 1.371 (+22.41%) compared to the soil without DO at Cd (II) concentrations of 20, 40, 60, 80, and 100 mg/kg, respectively. Biological accumulation coefficient also showed the same trend as the BCF. In all the treatments, the translocation factor was >1. Therefore, it was demonstrated that milk thistle had high potential for transferring Cd from root to shoot and reducing its concentration in the soil. Moreover, the study revealed that milk thistle had high potential for absorbing Cd in the soil contaminated with Cd and DO.